Sex Differences in Sport Remain When Accounting for Countries' Gender Inequality. (December 2016) - Balish, Shea M.; Deaner, Robert O.; Rainham, Daniel; Blanchard, Chris
The spectator lek hypothesis argues that sex differences in preferences for sport largely stem from evolved predispositions and thus should be universal or near universal, whereas socioconstructivist hypotheses argue that such sex differences are entirely socially constructed and thus should vary as a function of a society's gender inequality. To test these competing hypotheses, cross-national nested data were acquired from the International Social Survey Program (ss = 49, 729, ncountries = 34). Hierarchical linear modeling was used to examine whether sex differences in sport are universal or near universal when controlling for countries' gender inequality. Findings indicate that even when controlling for gender inequality, sex differences remain in reporting sport as one's most common activity, in watching sport, and in attending sport events and for agreeing with the statement that one plays sport to compete against others. Although this study was limited by the homogeneity of the sampled countries and the use of self-report measures, these findings nonetheless support the spectator lek hypothesis. Future research should examine case studies (e.g., matrilineal societies) that can specifically test the assumptions of the spectator lek hypothesis.